Digital Financial Literacy Among Young Adults in Malaysia - Wan Rasyidah Wan Nawang; Syadiyah Abdul Shukor (International Business Education Journal, 2023)
The financial industry has been impacted by the increased use and reliance on digital technologies, which has resulted in the digitalization of financial products, services, and providers. This transformation highlights the importance of individuals’ digital financial literacy (DFL). Accordingly, this study determines the prevalence of DFL among young adults in Malaysia. An online questionnaire was designed using Google Forms and a Uniform Resource Locator (URL) link was used to distribute the survey on several social media platforms. Respondents were selected using a convenience sampling and 229 responded to the survey. The survey sought to measure DFL in four dimensions: knowledge of digital financial products and services, awareness of digital financial risks, knowledge of digital financial risk control, and knowledge of consumer rights and redress procedures. The results show that Malaysian young adults score medium-high to high on all four dimensions of DFL and have a good understanding of DFL. This study is important for both academics and practitioners. It contributes to the limited knowledge in DFL, which is a new concept with little empirical evidence, and thus serves as a catalyst for future DFL research. As the world progresses towards digitalization, having DFL is essential. This study supports the government, educational institutions, and policy makers in developing financial literacy programmes and policies related to DFL towards improving the well-being of Malaysians and the national vision of shared prosperity to become a high-income nation by 2030.